Effect of nanofilled self-adhesive protective coating on color changes and surface roughness of composite resin - Rinastiti, Margareta; Widyastuti, Andina (Odonto : Dental Journal, 2023)
Background: Discoloration of composite restorations may affecting aesthetic appearance. The aging-process and surface roughness may influence color changes. A nanofilled self-adhesive protecting coating has been developed for coating tooth restoration and expected to prolong the longevity of restoration. To evaluate the effect of nanofilled self-adhesive protective coating on the surface roughness and color-changes of flowable and packable composite after aging condition. Methods: The total of 40 discs (15x2mm) and 60 boxes (20Ã—10Ã— 2mm) specimens from flowable and packable composite were used. A half of the specimens was coated by using protective-coating. The reflectance chromameter was used to measure the color baseline. Afterward, the specimens were subjected into aging process by immersing in artificial saliva and carbonated drink (37oC,7d). The color changes were calculated based on the [CIE L*a*b*].For surface roughness, box-shaped specimens were measured in fresh condition, after aging conditions. Results: The color change ranged from 0.49 to 2.31. Applying protective-coating was associated with a significant decrease in the color-changes and surface roughness after aging. The changes of three color coordinates resulted in significant differences for both composite, with and without protective coating application. Conclusion: The application of protective-coating decrease the color-changes and surface roughness of flowable and packable composite-resin.